2017
DOI: 10.1111/febs.14157
|View full text |Cite
|
Sign up to set email alerts
|

Cwp2 from Clostridium difficile exhibits an extended three domain fold and cell adhesion in vitro

Abstract: Colonization of the gut by Clostridium difficile requires the adhesion of the bacterium to host cells. A range of cell surface located factors have been linked to adhesion including the S‐layer protein LMW SLP and the related protein Cwp66. As well as these proteins, the S‐layer of C. difficile may contain many others. One such protein is Cwp2. Here, we demonstrate the production of a C. difficile strain 630 cwp2 knockout mutant and assess the effect on the bacterium. The mutant results in increased TcdA (toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Although CWPs involved in bacteria colonization have been identified, more CWPs need to be studied for their important roles in CDI and potential application in developing new therapeutics and prophylactics in C. difficile. Like other bacteria, C. difficile also possess multiple adhesins, and several CWPs have been previously characterized, including SlpA, Cwp2, Cwp6, CwpV, Cwp66, Cwp84 and Cwp19 (Waligora et al, 2001;Wright et al, 2005;Kirby et al, 2009;Dang et al, 2010;Reynolds et al, 2011;Bradshaw et al, 2017;Ferreira et al, 2017;Wydau-Dematteis et al, 2018). Although the exact role of each CWP in pathogenesis remains to be further elucidated, antibodies to many CWPs have been found in serum samples from CDI patients, and investigational vaccines targeting Cwp84 Sandolo et al, 2011) have been developed, indicating that certain CWPs are surface exposed in vivo and could be developed into vaccines (Pechine et al, 2005;Wright et al, 2008;Biazzo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CWPs involved in bacteria colonization have been identified, more CWPs need to be studied for their important roles in CDI and potential application in developing new therapeutics and prophylactics in C. difficile. Like other bacteria, C. difficile also possess multiple adhesins, and several CWPs have been previously characterized, including SlpA, Cwp2, Cwp6, CwpV, Cwp66, Cwp84 and Cwp19 (Waligora et al, 2001;Wright et al, 2005;Kirby et al, 2009;Dang et al, 2010;Reynolds et al, 2011;Bradshaw et al, 2017;Ferreira et al, 2017;Wydau-Dematteis et al, 2018). Although the exact role of each CWP in pathogenesis remains to be further elucidated, antibodies to many CWPs have been found in serum samples from CDI patients, and investigational vaccines targeting Cwp84 Sandolo et al, 2011) have been developed, indicating that certain CWPs are surface exposed in vivo and could be developed into vaccines (Pechine et al, 2005;Wright et al, 2008;Biazzo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the C. difficile S-layer in colonization, immunity, virulence and viability has been well-studied (Calabi et al, 2002;Pechine et al, 2005;Ausiello et al, 2006;Pechine et al, 2007;Kirk et al, 2017). Several other CWPs such as Cwp84, Cwp2, Cwp66, and CwpV have been investigated, and play important roles in host cell adhesion and immune system evasion during CDI (Waligora et al, 2001;Emerson et al, 2009;Kirby et al, 2009;Bradshaw et al, 2017;Wydau-Dematteis et al, 2018). Kirby et al (Kirby et al, 2009) identified a surface-associated protease, Cwp84, which cleaves SlpA precursor into mature form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the glycoside hydrolase domain of C. difficile S-layer-associated protein Cwp19 consisting of residues 28-388 has been determined to a high resolution. This is the sixth structure of the functional region of a protein from the S-layer of C. difficile to be determined after LMW SLP [40], Cwp84 [41,42], Cwp6 and Cwp8 [43] and Cwp2 [44]. We have identified a number of potential residues that are likely to be important active site residues and have partially characterised the activity of Cwp19-fr.…”
Section: Discussionmentioning
confidence: 99%
“…a LMW SLP: 3CVZ (Fagan et al 2009 ). b Cwp2: 5NJL (Bradshaw et al 2017a ). c Cwp8: 5J7Q (Usenik et al 2017 ).…”
Section: Slpamentioning
confidence: 99%